Mengelola Tekanan Akademik Melalui Nilai- Nilai Islam di Kalangan Mahasiswa - Putri, Almayra Ivana; Agustina, Fauziyah Cahyani; Khoerunnisa, Nadyla; Husnawati, Nurul (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
The purpose of this study is to examine how Islamic values can be optimized as a source of strength in managing academic stress among university students. The results are expected to contribute to the development of an academic stress management model based on Islamic values, relevant and applicable in higher education today. This research method uses a mixed methods approach with a sample of 35 Muslim students aged 20-25 years selected by simple random sampling. Data were collected through Likert scale surveys and open-ended responses, then analyzed descriptively and thematically. The results of this study are expected to contribute to the development of an academic stress management model based on Islamic values, relevant and applicable in higher education today. The increasing role of ikhlas values as a stress buffer, which may be related to the more collective Indonesian cultural context. Keywords : Islamic values, Academic pressure